Fluvial systems and their sedimentary models - Skaberne, Dragomir (Geologija, 1994)
The Slovenian geomorphologic and sedimentologic terminology for fluvial depositional environments is not established yet. Therefore a classification and the proposal for Slovenian names of fluvial sedimentary and erosional forms and influences controlling them are discussed. Attention is given to the problems of recognition of sedimentary environments in sedimentary rocks, and to fluvial sedimentary models.